2016
DOI: 10.1096/fj.201600530r
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits the production of proangiogenic 15(S)‐HETE by platelet cyclooxygenase‐1

Abstract: Regular consumption of low-dose aspirin reduces the occurrence of colorectal, esophageal, stomach, and gastrointestinal cancers. The underlying mechanism is unknown but may be linked to inhibition of angiogenesis. Because the effective doses of aspirin are consistent with the inhibition of cyclooxygenase-1 in platelets, we used liquid chromatography with tandem mass spectrometry analyses and immunoassays of human platelet releasates coupled with angiogenesis assays to search for the mediators of these effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 26 publications
7
44
1
1
Order By: Relevance
“…Platelets can produce significant amounts of TXA 2, PGE 2 , PGD 2 , 11‐, 12‐ and 15‐HETE dependent upon the activity of cytosolic group IV A PLA 2 , a widely expressed PLA 2 isoform (Kirkby et al, ; Rauzi et al, ). Below, we will discuss platelet and non‐platelet‐derived eicosanoids whose actions modulate platelet function and consequentially haemostasis and thrombosis (Figure ).…”
Section: Eicosanoids and The Fine Regulation Of Platelet Function Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets can produce significant amounts of TXA 2, PGE 2 , PGD 2 , 11‐, 12‐ and 15‐HETE dependent upon the activity of cytosolic group IV A PLA 2 , a widely expressed PLA 2 isoform (Kirkby et al, ; Rauzi et al, ). Below, we will discuss platelet and non‐platelet‐derived eicosanoids whose actions modulate platelet function and consequentially haemostasis and thrombosis (Figure ).…”
Section: Eicosanoids and The Fine Regulation Of Platelet Function Andmentioning
confidence: 99%
“…12‐HETE is the major 12‐LOX‐catalysed metabolite and the most abundant eicosanoid produced by platelets upon stimulation (Kirkby et al, ; Rauzi et al, ), but its effects on platelet function are not completely understood. Initial studies suggested that both 12‐HETE and 14‐hydroxy‐docosahexaenoic acid (14‐OH‐DHA), the 12‐LOX‐derived metabolite of DHA, inhibit platelet aggregation initiated by the TP receptor agonist U46619 (Croset et al, ).…”
Section: Eicosanoids and The Fine Regulation Of Platelet Function Andmentioning
confidence: 99%
“…also used an assay volume of 150 μl, albeit with different ratios of PRP to agonist (10,16). A few groups have used an assay volume of more than 150 μl (15,17,19), but most have reduced volumes of PRP or washed platelets to around 100 μl (9,11,2022). As a result, for the same volume of blood collected from a patient, a greater selection of agonists and concentrations may be studied using this assay that using LTA.…”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…The majority of this work concerns the characterization of platelet reactivity in the presence of antiplatelet therapies such as GPIIb/IIIa inhibitors (16,23) or dual anti-platelet therapy with ADP P2Y 12 antagonists plus aspirin (1013,17,21,22,25,26). Using these techniques, it is possible to produce concentration-response curves which can be used to evaluate the pharmacological action of these therapies.…”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…In fact, angiogenesis is a common target of many cancer chemopreventive agents including aspirin and curcumin . Mechanistically, aspirin inhibits the production of 11‐hydroxyeicosatetraeoic acid and 15 (S)‐ hydroxyeicosatetraenoic acid from platelets, which can induce endothelial cell migration and the formation of tubular structure . In addition, the proangiogenic heparanase is a novel target of aspirin .…”
Section: Complex Mechanisms For the Anticancer Effects Of Aspirinmentioning
confidence: 99%